Canadian Economic Evaluation of Budesonide-Formoterol as Maintenance and Reliever Treatment in Patients with Moderate to Severe Asthma - Elizabeth Miller; Malcolm R Sears; Andrew McIvor; Anna Liovas (Canadian Respiratory Journal, 2007)
OBJECTIVES: To compare the cost-effectiveness of budesonide-formoterol in a single inhaler used as both maintenance and reliever medication versus clinician-directed titration of salmeterol-fluticasone as maintenance medication, plus salbutamol taken as needed, in controlling asthma in adults and adolescents.